Transnational migration and the involuntary return of undocumented migrants across the Cambodian–Thai border. Issue 16 (10th December 2019) - Nurick, Robert; Hak, Sochanny
ABSTRACT: Migration from Cambodia is a major livelihood strategy for rural communities, with most rural families having at least one, usually younger, member migrating in search of work. The pervasive nature of this phenomenon relates to Cambodia's troubled political past, and the country's political economy that structures choice and opportunity. Under-investment in the agrarian economy together with unequal access to credit and productive resources leaves many rural Cambodians with little option but to migrate to boost family income. Thailand is the number one destination for rural Cambodians. Most have an undocumented status, putting them at risk of arrest and deportation. The return of more than 200, 000 migrants to Cambodia over a two-week period in 2014 was precipitated by the Thai military's seizure of power and migrants' fear of the consequences of political instability, given their still vivid historical memory of the Cambodian Khmer Rouge's reign of terror during the 1970s. Interviews with Cambodian migrants and members of their families are examined within a wider political and economic context to gain insight into migrants' motivations and decision-making. The expulsion of migrants from Thailand casts light on the compulsive nature of migration, despite the high risks and precarious conditions under which undocumented migration takes place.